2021
DOI: 10.1002/humu.24250
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating clinical phenotypic variability associated with the polyT tract and TG repeats in CFTR

Abstract: Biallelic pathogenic variants in CFTR manifest as cystic fibrosis (CF) or other CFTR‐related disorders (CFTR‐RDs). The 5T allele, causing alternative splicing and reduced protein activity, is modulated by the adjacent TG repeat element, though previous data have been limited to small, selective cohorts. Here, the risk and spectrum of phenotypes associated with the CFTR TG‐T5 haplotype variants (TG11T5, TG12T5, and TG13T5) in the absence of the p.Arg117His variant are evaluated. Individuals who received physici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…32,33 This variable clinical presentation associated with the 5T variant depends greatly on the number of TG repeats also present on the same allele. 34 Long-term studies on patients heterozygous for these variants are needed to better elucidate their risk for abnormal phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 This variable clinical presentation associated with the 5T variant depends greatly on the number of TG repeats also present on the same allele. 34 Long-term studies on patients heterozygous for these variants are needed to better elucidate their risk for abnormal phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…CF is an autosomal recessive disorder caused by pathogenic variants in the CFTR gene, which is also associated with CF‐related conditions such as pancreatitis and male infertility. Low‐complexity poly‐T and TG repeats within intron 9 of the CFTR gene can alter splicing of CFTR transcripts, and specific combinations of these repeats with other variants affect clinical manifestation of CF‐related disorders (Nykamp et al, 2021 ). Most individuals have poly‐T genotypes consisting of 5, 7, or 9 Ts, and the presence of 5 Ts is known to disrupt the function of CFTR .…”
Section: Resultsmentioning
confidence: 99%
“…With a reported allele frequency of 4.2%, 5T is quite common in the general population. Nykamp et al found 5T to be enriched in persons tested for a CF‐related indication (e.g., congenital bilateral absence of the vas deferens or chronic sinopulmonary issues) when compared to persons screened for non‐CF indications, such as routine carrier screening 30 . The penetrance of 5T is known to be impacted by an increasing number of linked TG repeats 31 .…”
Section: Discussionmentioning
confidence: 99%
“…routine carrier screening. 30 The penetrance of 5T is known to be impacted by an increasing number of linked TG repeats. 31 The most common VCC in our cohort was 5T-12TG.…”
Section: Studies Of Genetic Counseling Service Delivery In Numerousmentioning
confidence: 99%